2022
DOI: 10.3389/fimmu.2022.828447
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins and Ischemic Stroke

Abstract: Ischemic stroke after cerebral artery occlusion is one of the major causes of chronic disability worldwide. Interleukins (ILs) play a bidirectional role in ischemic stroke through information transmission, activation and regulation of immune cells, mediating the activation, multiplication and differentiation of T and B cells and in the inflammatory reaction. Crosstalk between different ILs in different immune cells also impact the outcome of ischemic stroke. This overview is aimed to roughly discuss the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 176 publications
3
119
0
3
Order By: Relevance
“…We found that caspase-1 and IL-10 were elevated in patients with unfavorable outcomes when compared to those with favorable outcomes. IL-10 is secreted by numerous cells of the CNS after injury and has been shown to play a protective role by reducing cytokine activity, proinflammatory activity, and apoptosis [75,76]. Additionally, IL-10 inhibits IL-2 activity, and has been shown in numerous studies to be increased after stroke or TBI [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…We found that caspase-1 and IL-10 were elevated in patients with unfavorable outcomes when compared to those with favorable outcomes. IL-10 is secreted by numerous cells of the CNS after injury and has been shown to play a protective role by reducing cytokine activity, proinflammatory activity, and apoptosis [75,76]. Additionally, IL-10 inhibits IL-2 activity, and has been shown in numerous studies to be increased after stroke or TBI [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Over-activation of microglial cells releases various pro-inflammatory cytokines that exacerbate cerebral ischemia-reperfusion (I/R) injury [148,149]. There are many different cytokines reported as biomarkers for cerebral ischemia, such as IL-1β, IL-6, IL-8, IL-12, IL-15, IL-16, IL-20, IL-18, IL-23/IL-17, and so on, which play a pro-inflammatory role after ischemic stroke; ILs that have anti-inflammatory effects on ischemic stroke include IL-2, IL-4, IL-10, IL-13, IL-19, IL-33, and so on, as reported recently [150]. In 2019, ischemic stroke affected approximately 77.2 million individuals [151].…”
Section: Role Of Fatty Acids In Microglial Polarization In Cerebral I...mentioning
confidence: 67%
“…[23][24][25] warrants further investigation. Classically, IL-4 and related T h2 -type immune responses were thought to oppose pro-atherogenic T h1 activities, and indeed IL-4 has been demonstrated to aid in tissue recovery/damage resolution following ischemic stroke [26]. Yet, the simplified paradigm of T h2 and IL-4 as purely athero-protective, inflammation-resolving has been challenged by other mechanistic and clinical data implicating these allergic-type responses (e.g.…”
Section: Discussionmentioning
confidence: 99%